'Chinese academia wouldn't be tolerant of my research': gay academics' concerns about conducting queer research in China. Issue 4 (3rd April 2023) - Cui, Le
Abstract: Drawing on interviews with 40 Chinese gay academics, this paper reveals participants' concerns about conducting queer research in China. These include sexual-identity exposure, difficulty in publishing research and receiving funding, as well as marginalisation within university departments. Informed by Irvine's conceptualisation of sexuality research as dirty work, this research examines the operation of heteronormativity in the constitution of queer research as dirty work. It shows that heteronormativity is intrinsic to research censorship by authorities, as repressive politics pursue regime maintenance and regulate difference. It is argued that Chinese academia is a heteronormative space in which queer research is constrained by the institutions and the Party-state. By teasing out the nuances in participants' experiences of research censorship, this paper highlights the complexity of power at play, which is far from a one-way relationship of authorities exerting power over researchers. Institutions exert power over queer researchers and simultaneously submit to the higher-level power of the Chinese Communist Party political system; at the same time, queer researchers who are governed by heteronormativity and political control can express their agency and resist the censorship.